MEDIUM POWER ELECTRICAL TRANSFORMERS DESIGNED AND MANUFACTURED BY ELECTROPUTERE CRAIOVA FOR POWERING ELECTRICAL FURNACES USED IN METALLURGY (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
The paper presents the differences between transformers for powering electric furnaces and mains transformers. It presents the secondary voltage regulation schemes and the types of secondary terminals generally used in such transformers. This is followed by a presentation of the transformers designed to power electric furnaces, designed at ICMET and manufactured at ELECTROPUTERE Craiova for the Romanian metallurgy industry between 1978 and 1991.
Keywords: Electrical transformers; Electric arc furnaces; Electric reduction furnaces; Vacuum degassing installations